Central Nervous System Nocardiosis Due to Nocardia farcinica - Kate Zha; Michelle Bahrain; Jasvinder Singh; Jeffrey Iding; Teresa Wojtasiewicz; Christopher J. Haas (Annals of Internal Medicine: Clinical Cases)
Nocardia is an opportunistic aerobic, filamentous, gram-positive branching rod that infects immunocompromised hosts. Infections usually stem from the pulmonary, integumentary, or, rarely, gastrointestinal systems. Nocardia farcinica has a noted predilection for neural tissue, thought to represent secondary dissemination from prior infection.